2011
DOI: 10.1029/2010jb007965
|View full text |Cite
|
Sign up to set email alerts
|

The high-pressure electronic spin transition in iron: Potential impacts upon mantle mixing

Abstract: [1] At the Rayleigh number appropriate to Earth's mantle, radial heat transport is dominated by solid state thermal convection. Because of the large number of physical properties required to determine the Rayleigh number, and because these properties are expected to be (perhaps strong) functions of pressure and temperature (P-T), laboratory measurements of them under the high pressure and temperature conditions that occur in the deep Earth are of fundamental importance. Recent experimental data demonstrate tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
35
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 58 publications
6
35
0
Order By: Relevance
“…These signatures have been widely reported in previous seismic tomography studies such as the disruption of P wave image below some hot spots (Zhao, 2007), the global disruption of P wave structure (van der Hilst and Kárason, 1999) at ∼1700 km depth, anti-correlation between shear velocity and bulk sound velocity around middle lower mantle (Simmons et al, 2010), and discrepancy between P and S wave model at the origin depth of thermal plumes (Boschi et al, 2007). Here we further found that iron-spin transition may control the formation of LLSVPs, a signature of the spin transition from geodynamic aspect.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…These signatures have been widely reported in previous seismic tomography studies such as the disruption of P wave image below some hot spots (Zhao, 2007), the global disruption of P wave structure (van der Hilst and Kárason, 1999) at ∼1700 km depth, anti-correlation between shear velocity and bulk sound velocity around middle lower mantle (Simmons et al, 2010), and discrepancy between P and S wave model at the origin depth of thermal plumes (Boschi et al, 2007). Here we further found that iron-spin transition may control the formation of LLSVPs, a signature of the spin transition from geodynamic aspect.…”
Section: Discussionsupporting
confidence: 74%
“…T is temperature perturbation; p is dynamic pressure; K T is isothermal bulk modulus. When iron-spin transition occurs, the new ρ can be written in the form that is similar to Shahnas et al (2011):…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For comparison, the spin crossover in Fp increases the density of a chemically homogeneous pyrolitic mantle by ∼0.7%. It is a smooth and broad feature that should enhance convection in a chemically uniform mantle (22)(23)(24), especially in the spin crossover zone, which spans most of the lower mantle. This broad spin crossover also seems consistent with the lack of seismological evidence of a compositional transition and associated thermal boundary layers (39,40) in the mid-lower mantle.…”
Section: Significancementioning
confidence: 99%
“…Therefore, its effects on aggregates are more elusive and indirect. For instance, the associated density anomaly can invigorate convection, as demonstrated by geodynamics simulations in a homogeneous mantle (22)(23)(24). The bulk modulus anomaly may decrease creep activation parameters and lower mantle viscosity (10, 24, 25) promoting mantle homogenization in the spin crossover region (24), and anomalies in elastic coefficients can enhance anisotropy in the lower mantle (16).…”
mentioning
confidence: 99%